Wine consumers' subjective responses to wine mouthfeel and understanding of wine body. (September 2017) - Niimi, Jun; Danner, Lukas; Li, Luxing; Bossan, Hélène; Bastian, Susan E.P.
Abstract: Wine mouthfeel is considered important for wine quality by experts, while consumers understanding of mouthfeel and the role of wine body in their wine choice is unknown. One experiment determined the influence of intrinsic wine mouthfeel on consumers' wine liking and emotions, and the other, how consumers understand the term wine body. The first experiment used a 2 astringency level × 2 body level experimental design. The samples were base wine with; nothing added (control), added xanthan gum (for increased body), added grape seed extract (GSE, for increased astringency), and with both added xanthan gum and GSE. The consumer taste trial (n = 112) indicated that wine with increased body did not influence wine liking and emotions; while increased astringency decreased liking and elicited more intense negative emotions. The second experiment examined consumers' knowledge of wine body through an online survey (n = 136). Consumers described wine body most frequently using words such as flavour, fullness, and strength. Wine body was therefore understood by consumers predominantly as a holistic multi-sensory perception of flavour. Wine flavour was indicated by consumers to be the most important factor driving purchase decisions followed by balance of flavours and wine body. It is crucial that wine professionals carefully communicate wine characteristics to consumers to prevent possible misunderstandings such as the meaning of wine body and as a result better meet consumer expectations. In future, the term body may benefit from a clearer definition for academic research as well as industry. Graphical abstract: Highlights: Changes in astringency of wine was a determinant in consumers liking and emotions. Increases in body by addition of gum had no influence on consumers liking or emotions. Wine body was understood by consumers as a holistic perception of flavour and intensity, not only mouthfeel.